ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN TELEKOMUNIKASI - Apriani, Mia; Lestari, Nurlaela Eva Puji; Hidayat, Aris (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2023)
The rapid growth of the telecommunications industry and fierce competition make assessing the financial performance of telecommunications companies increasingly important. This study analyzes the financial performance of telecommunications companies listed on the Indonesia Stock Exchange (IDX) in the period 2018-2022 with a special focus on liquidity ratio analysis. The purpose of this study is to identify companies that have optimal financial performance and understand the development of their financial position. A descriptive quantitative non-statistical approach was applied to this study. Financial data from five telecommunication companies listed on the IDX were collected and analyzed to assess liquidity performance during the study period. The results showed PT Telkom Indonesia (Persero) Tbk had the best liquidity performance with an increase in cash and cash equivalents from 2018 to 2022. However, other companies experience fluctuations in liquidity ratios. To improve liquidity performance, these companies need to optimize the use of current assets, monitor current debt, and improve the cash cycle. This research provides an overview of the financial performance of telecommunications companies on the IDX and can be used by investors in making investment decisions. PT Telkom Indonesia (Persero) Tbk shows the best liquidity performance, while other companies need to improve their liquidity performance.